An approach for the crash safety assessment of smaller and lightweight vehicles. (May 2021) - Davies, Huw C.; Bastien, Christophe
Abstract: Concerns around the externalities resulting from transport are leading to a reassessment of our mobility options. By reference to policy priorities, it is concluded that there will be an emerging demand for smaller and lighter vehicles. Within Europe these will be of the L6e and L7e category. However, the crash safety of these vehicles presents an impediment to their broader commercialisation, acceptance, and further development. The authors identify a number of concerns associated with the approaches to crash safety assessment being discussed and promoted by stakeholders. These concerns include: cascading down M1 category test requirements to the L6e and L7e category would be inefficient as there is little inclination at present to develop, manufacture and market small and lightweight M1 category vehicles; subjecting the L6e and L7e category vehicles to the same crash test and test performance requirements as an M1 category passenger car would not result in comparable performance in single vehicle or vehicle-to-vehicle collisions; and vehicle use cases will differ leading to different accident patterns and questioning the efficacy of the existing M1 category test approach for these smaller and lighter vehicles. To improve the safety of lightweight vehicles would require an innovative test and assessment framework that provides benefits to consumers, producers and society. As a contribution to this framework, an approach is proposed for the assessment of crashworthiness that: responds to the immediate concerns around the safety performance in frontal collisions; aligns with the emerging capabilities of the L-category industry; and provides the consumer with a new mobility option that responds positively to key externalities associated with our use and consumption of transport. The proposed assessment is discussed and is shown to provide equivalent compartment strength to a mid-sized M1 category passenger car – thereby addressing a key concern about compartment integrity in collisions with larger and heavier vehicles. Highlights: Through reference to policy, identifies the key externalities driving transport change. Discusses the safety problems in accidents presented by smaller and lighter vehicles. Develops a proposed assessment for crashworthiness of smaller and lightweight vehicles. Discusses benefits of proposed approach to consumers, producers and society.